Efeito da cafeína no desenvolvimento de Aedes aegypti (Diptera: Culicidae): o significado biológico das alterações do padrão de síntese de esterases - Pólo, André Martins [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The mosquito Aedes aegypti is a vector of human disease-causing virus, including dengue, dengue hemorrhagic fever and yellow fever. The transmission of these diseases is made by the adult females, which require blood repast for completing their eggs maturation. When females bite sick individuals and later bite healthy individuals, they transmit the virus absorbed with the blood from the first. Several studies have shown that treatment with caffeine (CAF) blocks development and kills A. aegypti in the larval phase, preventing the production of adults and, consequently, the transmission of the mentioned diseases. In addition, preliminary work indicated that CAF treatment of A. aegypti changes the pattern of synthesis of esterase enzymes. The esterase enzymes play important roles in various physiological processes of the organisms, including among them the control of the metamorphosis of insects. In the present study, the esterases were analyzed in polyacrylamide gels stained with α and ß naphthyl acetates and Fast Blue RR. The samples were prepared with L2, L3 and L4 larval stages, pupae and adults. However, considering that the L4 stage was the one that allowed better observation of the bands, the study was almost restricted to it. The comparison of the treated and control mosquitoes involved observations of the presence and frequency of the esterase bands in the gels. The degree of expression of the bands was also analyzed on the basis of the staining intensity evaluated by the Global Lab Image computer program. The analysis showed that CAF changed five β-esterase bands (EST-17A to EST-21) and a group of α-esterase bands (EST-12 to EST-14). The bands EST-17A to EST-20 showed reduction in both characteristics, while EST-21 and the α-esterases showed increase of them. In view of the changes occurred in the degree of expression of the esterases, parallel to the larval development block we thought in the hypothesis that these esterases ...

O mosquito Aedes aegypti é vetor dos vírus causadores de doenças humanas entre as quais incluem-se a dengue, a dengue hemorrágica e a febre amarela. A transmissão dessas doenças é feita pelas fêmeas adultas, as quais necessitam de repasto sanguíneo para amadurecimento de seus óvulos. Ao picar indivíduos doentes e depois indivíduos não infectados, as fêmeas transmitem os vírus absorvidos dos primeiros, juntamente com o sangue. Vários estudos mostraram que o tratamento com cafeína (CAF) bloqueia o desenvolvimento e mata A. aegypti na fase larval, impedindo a produção de adultos e, consequentemente, a transmissão das doenças mencionadas. Paralelamente, trabalhos preliminares indicaram que o tratamento do mosquito com CAF altera o padrão de síntese das enzimas esterases. São enzimas que desempenham papel importante em vários processos fisiológicos dos organismos, estando inclusive envolvidas no controle da metamorfose dos insetos. No presente trabalho, as esterases foram analisadas em géis de poliacrilamida corados com α-naftil e β-naftil acetatos e Fast Blue RR. As amostras foram preparadas com larvas L2/L3, L4, pupas e adultos, porém, tendo em vista que a fase L4 foi a que permitiu melhor observação das bandas, o estudo praticamente restringiu-se à mesma. A comparação das amostras dos mosquitos tratados e controle envolveu a observação da presença e da frequência das bandas esterásicas nos géis. Foi também analisado o grau de expressão das bandas com base na intensidade de coloração avaliada pelo programa computacional Global Lab Image. A presente análise mostrou que a CAF altera cinco bandas β-esterásicas (EST-17A a EST-21) e um grupo de bandas α-esterásicas (EST-12 a EST-14). As bandas EST-17A a EST-20 apresentaram redução em ambas as características, enquanto EST-21 e as α-esterases apresentaram aumento. Tendo em vista as variações do grau de expressão das esterases, paralelamente ao ...
Keywords: Insetos Genética; Inseto - Hormonios; Aedes aegypti; Esterases; Hormonios juvenis; Cafeína; Insect hormones